Mental health consequences of long-term stays in refugee camps: preliminary evidence from Moria - Willemine van de Wiel; CASTILLO LABORDE, CARLA CECILIA; I. Francisco Urzúa; Michelle Fish; Willem F. Scholte (My University, 2021)
Abstract Background Ever since the implementation of the EU-Turkey deal, most refugees that enter Greece via sea are confined to the island on which they arrive until their asylum claims are adjudicated, where they generally reside in camps. Some of these camps have detention-like characteristics and dire living conditions, such as Moria camp on the island of Lesbos, Greece. Aid-organizations have stated that the situation in camp Moria deteriorates the mental health of its inhabitants and there is qualitative evidence to support this. This study explores the quantitative relationship between the incidence of acute mental health crises and the length of stay in the camp. Methods A cross-sectional study was conducted using routinely collected data on 856 consultations of 634 different patients during 90 nights at an emergency clinic in Moria camp. Logistic regression analysis was used to explore whether the length of stay in the camp was predictive of the occurrence of an acute mental health crisis. Results Of the 634 patients, the majority were men (59·3%), the average age was 23·2 years [0–71], and 24·3% was < 18 years. 25·5% (n = 218) of consultations were related to mental health problems; 17·0% (n = 37) of these met the study’s case definition of an acute mental health crisis. Such crises were positively associated with the length of stay in the camp (p = 0·011); the odds ratio of a mental health crisis increases with 1·03 for every 10% increase in days of residence in the camp. This is notable when considering the average length of stay in the camp is 71 days. Conclusion This study offers quantitative support for the notion that the adverse conditions in Moria camp deteriorate the mental health of its inhabitants as suggested in qualitative research. Although this study does not provide evidence of causality, it is likely that the poor and unsafe living conditions, challenging refugee determination procedures, and a lack of mental health services in the camp are significant contributing factors. We urgently call for Europe’s policymakers to honour the ‘51 Geneva refugee convention and terminate the neglectful situation on the Greek archipelago.
Keywords: refugees; camp; greece; containment; mental health; crisis; adult; cross-sectional studies; female; greece; humans; male; mental health; refugee camps; refugees; turkey; young adult; adult; cross-sectional study; epidemiology; female; greece; human; male; mental health; refugee; refugee camp; turkey (bird); young adult